Effectiveness of the Implementation of the Law on General Provisions and Tax Procedures Related to the Authority of Investigators in Tax Crimes - Rizki, Pebriana; Purnawan, Amin (UNISSULA Semarang, 2025)
Article 23A of the Constitution of the Republic of Indonesia clearly stipulates that